PERBEDAAN HARGA SAHAM PERUSAHAAN SEBELUM DAN SESUDAH LISTING PADA LQ 45 DI BURSA EFEK INDONESIA - Dosen Fakultas Ekonomi Manajemen UNIBA, Sudarwati Eny Kustiyah (MAJALAH ILMIAH GEMA, 2014)
The stock exchange is the value of a stock that reflects the wealth of the company that issued the shares, which change or fluctuate depends on the new accepted information. The development of a companyâs stock exchange reflects the value of the company shares, so the wealth of the shareholders shows from the market price of the shares . The purpose of this study is to know and to analyze the differences of the stock exchange before and after listing on the listing LQ45 , as well as to determine the effect of stock prices before and after listing partially and simultaneously influence the stock trading volume. The population of the study is LQ45; is stock listed company and out of membership LQ45 calculation during the period of August 2012 to January 2013; PT. State Savings Bank Tbk , PT. Delta Dunia Makmur Tbk , PT . Gajah Tunggal Tbk , PT . Krakatau Steel Tbk , and PT . Salim Ivomas Pratama Tbk. The data collecting technique is library research; the researcher takes the data from related literatures or books. Data are taken from the following website: http//www.idx.co.id and: http // www.financeyahoo.com. The data analysing technique is simple linear regression analysis and analysis of variance (ANOVA). The result of the study shows differences in stock exchange before and after listing the following companies; State Savings Bank Tbk, PT Delta Dunia Makmur Tbk, PT Gajah Tunggal Tbk, and PT Salim Ivomas Pratama Tbk. While there is no significantly different in the company of PT. Krakatau Steel Tbk between the stock exchange before and after listing. To State Savings Bank Tbk and PT. Delta Dunia Makmur Tbk, variables before listing contribute significant influence toward the volume of trade, while the variables after listing shows no significant influence toward the volume of trade. Whereas to PT. Gajah Tunggal Tbk and PT. Salim Ivomas Pratama Tbk, variables before and after the listing has no significant effect on the volume of trade. While to PT Krakatau Steel Tbk, variables before and after the listing show no significant influent toward the volume of trade. Keywords : Stock Price , Listing , LQ 45 and IDX